Revolusi Kehidupan: Adaptasi Komunitas Orang Nias di Kota Medan (1980-2010) dalam Bingkai Sejarah - Laia, Suka Damai; Fitri, Hadiani; Sumantri, Pulung (Medan Resource Center, 2023)
The aim of this research is to examine the adaptation of the Nias people in the city of Medan from 1980 to 2010 from a historical perspective. Data collection techniques employed in this study include observation, interviews, and document analysis. The processed data sources consist of primary and secondary data. The research method utilized is qualitative. The results of this study indicate that the adaptation of the Nias people in Medan, as observed from their skills in adjusting, is evident in their survival, maintaining their existence, and interacting to be accepted. This adaptation enables the Nias people to establish good and harmonious relationships with the Medan community. The success of the adaptation by the Nias people and the Medan community is influenced by supporting factors, such as awareness of their position in the environment and education. In addition to supporting factors, there are also hindering factors for the adaptation process, namely, cultural and language barriers.